Counselling on smoking cessation in primary care from the population perspective in two regions of the Russian Federation. (11th May 2021) - Kashutina, M; Kontsevaya, A; Mckee, M; Leon, D
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): This study was conducted as part of the International Project on Cardiovascular Disease in Russia (IPCDR). IPCDR is supported by the Wellcome Trust [100217/Z/12]; the Norwegian Ministry of Health; the Norwegian Institute of Public Health; UiT, The Arctic University of Norway. Background. Smoking is one of the main risk factors for noncommunicable disease, which account for about 71% of the world"s population mortality. The prevalence of smoking in Russia is 27.3% totally and average 37% in males. One of the effective strategies smoking cessation is counselling in primary care facilities. Purpose. Identify the frequency of counseling on smoking cessation in primary care from the population perspective in two regions of Russia and determine the socio-economic and behavioural factors associated with receiving advice on smoking. Methods. The study was carried out within the framework of the international scientific project "Know your heart" (2015-2018). A representative sample of residents of Novosibirsk and Arkhangelsk aged 35 to 69 years was included in the study. The frequency of getting advice on smoking cessation was analyzed among those respondents who have contacts with the healthcare system over the last year (n = 3320) and among those who are currently smokers (n = 738). Data were analyzed using SPSS v.17 and Jamovi v.1.6.8. Factors associated with the chance of getting were analyzed by binomial logistic regression analysis. The reliability of regression model was assessed using ROC analysis. Results. Only 491 responders (66.5%) who smoked and visited primary care facilities received advice on smoking cessation. Females were significantly less likely to receive counselling compared with males (Odds Ratio (OR) = 0.41; 95% Confidence Interval (CI) 0.27-0.60; p˂0.001), people aged 65+ compared with age group 35-44 (OR = 0.37; 95% CI 0.16-0.82; p = 0.014), working persons compared with pensioners (OR = 0.58; 95% CI 0.35-0.98; p = 0.041). Obesity (BMI = 30.0-34.9) significantly increased the chance of getting advice on smoking cessation compared with normal body mass (OR = 2.05; 95% CI 1.19-3.52; p = 0.010), as well as visits the GP (for visiting GP 1-2 times a year: OR = 1.66; 95% CI 1.12-2.46; p = 0.011; for visiting GP 3-4 times a year: OR = 3.35; 95% CI 1.76-6.36; p˂0.001; for visiting GP≥5 times a year: OR = 2.94; 95% CI 1.41-6.13; p = 0.004). Other types of contacts with healthcare system included in the analysis (visits to other specialists, hospitalizations, ambulance calls during previous 12 months) were not associated with the chance of getting advice on smoking quitting. The accuracy of the obtained regression model was 62.13 (p˂0.001). ROC analysis showed that the sensitivity of the model is 89.2%, specificity is 31.6%, the area under the ROC curve (AUC) is 0.710 ± 0.020 (95% CI 0.67-0.75) that corresponds to the good quality of the model. Conclusion. The healthcare system needs to be more proactive in conducting counseling on smoking cessation. Gender, age, BMI, visit to a GP were associated with receiving counseling on smoking cessation. More attention should be paid to women, elderly people and men with normal BMI. Other specialists except GPs also should pay attention to the patients smoking habits and give advice.